MERDEKA BELAJAR DALAM PERSPEKTIF KONSTRUKTIVESME DAN PROGREFISME SEKOLAH SERTA REALITAS SOSIAL - Yogi Alansyah Harahap; Amril M (STAIN MAJENE, 2024)
The aim of this study is to find out how constructivism, progressivism, and school reality influence responses to the idea of free learning. This type of research is qualitative and uses descriptive analysis and library study methods to gather data. Constructivism is a philosophical perspective that argues that knowledge is not something absolute and develops through interaction with others, communities, and environments. The theory of progressivism comes from John Dewe. Education must be socially oriented because students are seen as part of society. In the real world, school life is always changing, and so many complex processes are driving it. Therefore, schools can be seen as both static and dynamic parts of society.